1995
DOI: 10.1029/95wr01485
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Velocity Frequency Distributions in Stream Reaches

Abstract: The quantification of management impacts on fish populations requires a reliable estimation of the local hydraulic habitat variability. In the case of complex natural flows, deterministic hydraulic models are expensive and not adapted to the description of local velocities. Statistical descriptions of the velocity distribution as a function of easily obtained input variables are therefore an attractive alternative. Existing velocity data on several French stream segments with intermediate-to large-scale roughn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 24 publications
1
103
0
2
Order By: Relevance
“…In our study, streams of France and Virginia had similar ranges of Froude numbers, even though reaches in Virginia were generally narrower, shallower and slower flowing (see Methods). This variable also integrates the spatial diversity of point hydraulic variables (bottom shear stress, current velocity) in stream reaches (Lamouroux et al 1992(Lamouroux et al , 1995. Therefore, our results indicate that dimensionless physical variables reveal common properties of systems of different sizes, and are potential predictors of ecological similarities in these systems (Statzner et al 1988, Heede andRinne 1990).…”
Section: Implications For Predictive Models In Community Ecologymentioning
confidence: 88%
“…In our study, streams of France and Virginia had similar ranges of Froude numbers, even though reaches in Virginia were generally narrower, shallower and slower flowing (see Methods). This variable also integrates the spatial diversity of point hydraulic variables (bottom shear stress, current velocity) in stream reaches (Lamouroux et al 1992(Lamouroux et al , 1995. Therefore, our results indicate that dimensionless physical variables reveal common properties of systems of different sizes, and are potential predictors of ecological similarities in these systems (Statzner et al 1988, Heede andRinne 1990).…”
Section: Implications For Predictive Models In Community Ecologymentioning
confidence: 88%
“…While empirical models of variation in broad morphometric channel variables have been in existence for many years, it is only recently that these statistically based techniques have been applied to model habitat hydraulics at the reach or "mesohabitat" scale. It has been suggested that at the reach scale, statistical hydraulic models can provide estimates of the frequency distribution of hydraulic variables, when given simple inputs such as mean river velocity, depth, and width (Lamouroux et al 1995(Lamouroux et al , 1999. Statistical techniques have shown that consistent patterns of such distributions appear among different streams.…”
Section: Abiotic Habitat Modelingmentioning
confidence: 99%
“…Simplified alternative to Phabsim, supported by statistical analysis of about one hundred Phabsim (Evha for the French version) study sites simulations Lamouroux et al (1995Lamouroux et al ( , 1998 demonstrated that hydraulics variables distributions like velocity or depth can be derived from reach values of hydraulic geometry. In the logical extension of these works, the idea of similar results with the common outputs of Phabsim modelling (i.e.…”
Section: Validation At Complex Fish Community Levelmentioning
confidence: 99%
“…They are based on hydraulic statistical models (Lamouroux et al 1992(Lamouroux et al , 1995 coupled with local multivariate fish habitat models described above. The hydraulic statistical models are tools that predict the frequency distribution of velocity or depth in a stream reach with a simplification of the physical measurements.…”
Section: Validation At Complex Fish Community Levelmentioning
confidence: 99%